2009
DOI: 10.1098/rsbl.2009.0290
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity in probabilistic reaction norms for maturation in a salmonid fish

Abstract: The relationship between body size and the probability of maturing, often referred to as the probabilistic maturation reaction norm (PMRN), has been increasingly used to infer genetic variation in maturation schedule. Despite this trend, few studies have directly evaluated plasticity in the PMRN. A transplant experiment using whitespotted charr demonstrated that the PMRN for precocious males exhibited plasticity. A smaller threshold size at maturity occurred in charr inhabiting narrow streams where more refuge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 17 publications
1
45
1
Order By: Relevance
“…With respect to plasticity, Jonsson et al [35,36] noted that the threshold size at maturity in Atlantic salmon was affected by both water temperature and food quality. In addition, Morita et al [21] showed in a transplant experiment that the threshold size at maturity in male charr varies with river width and temperature. However, it is difficult to explain why the plasticity affected the divergence of threshold size at maturity in males, which is related to migration cost.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to plasticity, Jonsson et al [35,36] noted that the threshold size at maturity in Atlantic salmon was affected by both water temperature and food quality. In addition, Morita et al [21] showed in a transplant experiment that the threshold size at maturity in male charr varies with river width and temperature. However, it is difficult to explain why the plasticity affected the divergence of threshold size at maturity in males, which is related to migration cost.…”
Section: Discussionmentioning
confidence: 99%
“…For example, water temperature often decreases with increasing altitude, so it can also affect the diversity of threshold size at maturity in males (e.g. [21,22]). Thus, to test the hypothesis that migration cost is a general factor in shaping the diversity of threshold traits, the effects of migration costs on the threshold traits must be quantified under a sampling design that considers multicollinearity among environmental factors.…”
Section: Introductionmentioning
confidence: 99%
“…As the phenotype changes along the positively linear reaction norm, the fitness of the genotype (dashed lines) may change as well, in a linear (w 1 ) or nonlinear (w 2 ) manner, Incidence male parr maturity Probability of maturing Length (mm) Weight (g) Figure 8 Threshold reaction norms for the adoption of alternative life histories: (a) hypothesised genetic variability in reaction norm switchpoints between life histories A and B within a single population (re-drawn from Hazel et al, 1990); (b) genetic differences in reaction norms for parr maturity in male Atlantic salmon, Salmo salar, as a function of growth rate (weight at 7 months) (original source: Piché et al, 2008); and (c) environmental differences in reaction norms for maturity in white-spotted char, Salvelinus leucomaenis, as a function of growth rate (length at 1 þ years) (original source: Morita et al, 2009). or it may remain constant (w 3 ). As Figure 10 is also meant to illustrate, changes in fitness may be realised irrespective of whether the reaction norm has a non-zero slope or not.…”
Section: Issues Arisingmentioning
confidence: 99%
“…If the maturation process is influenced by variables not included in the statistical estimation of the PMRN, shifts in the position of the PMRN over time may not necessarily indicate genetic changes [23,27]. Indeed, shifts in the position of a PMRN in response to selection pressures in the wild might always be owing to some unaccounted for factor (e.g.…”
Section: Introductionmentioning
confidence: 99%